PROFESI DAN PROFESI HUKUM DALAM KERANGKA MASYARAKAT MODERN DI ERA DIGITALISASI - Ahmad Ikmaluddin Chafid; M. Choirun Naja; Ahmad Rizky Hidayat; Novan Zainuri (JURNAL ILMIAH NUSANTARA, 2024)
The legal profession, which includes various roles such as advocate, judge, prosecutor, police, notary, legal consultant and mediator, has its own characteristics compared to other professions. In the era of digitalization, the legal profession faces new challenges and opportunities that require integrity, honesty, authenticity, responsibility, moral independence and moral courage as basic values. Franz Magnis Suseno stated that these five moral values ​​are essential in forming an ideal legal professional personality. The legal profession is closely related to law enforcement and human rights in Indonesia, involving institutions such as the judiciary, prosecutor's office, police, Supreme Court and Constitutional Court. Digitalization is affecting legal practice, requiring legal professionals to be adaptive to technology and social change. In addition to their traditional roles, each legal profession has a unique contribution to make in modern society, which includes providing protection, law enforcement, consultation, and mediation. A deep understanding of the characteristics and ethics of the legal profession as well as adaptation to the era of digitalization is very important to maintain integrity and effectiveness in law enforcement.